Comparative Knowledge Gained from Online and Face-to-Face Learning Modes in Management Courses in Nepal - Sthapit, Arhan; Shrestha, Bikash (Journal of Business and Social Sciences Research, 2020)
The paper aimed at examining the perceived difference between knowledge gained from online and face-to-face learning modes as a result of the intensities (viz., high and low) of comparative interaction level and ease of attending the classes, in the context of management courses in Nepal. Based on the survey (complete enumeration) of all management students (n=224) attending the online classes at Nepal Open University from 5th to 25th Jan., 2020, the study applied descriptive statistics and factorial ANOVA using the General Linear Model in analysing data to pursue the research objectives. Nepalese management students’ experience with their present online classes in terms of the knowledge gained was found to be equivalent to their previous experience with the face-to-face mode. It also discovered that intensities of the comparative interaction level and comparative ease of attending classes had a significant impact on comparative knowledge gained. The findings should offer instrumental inputs to design effective higher education policies blending the online and face-to-face learning modes.